Postmodern elements in two novels: Mohja Kahf’s the girl in the tangerine scarf and Mohsin Hamid’s the reluctant fundamentalist - Abdullah, Suhaila (MNNF Publisher, 2017)
This qualitative research studies postmodernism, postmodern culture and the postmodern mind in two novels namely Mohja Kahf’s The Girl in the Tangerine Scarf (2009) and Mohsin Hamid’s The Reluctant Fundamentalist (2007). By focusing on postmodern elements, this research investigates the lives of immigrants who came from South Asia and Syria, as well as the major challenges these immigrants encounter in adapting to American culture. Immigrants face problems such as a yearning for home, trying to find a sense of belonging in a new land and a sense of displacement. They are also confronted by additional challenges while trying to navigate postmodern American culture.